Comparative Analysis Of The Fulfillment Of Normative Rights For Workers At The Time Of Termination Of Employment - Dwany Linca Iswanto; Miftakhul Huda (JURNAL HUKUM SEHASEN, 2024)
This study aims to determine the ratio legis of Law No. 6 of 2023 and the suitability of changes in the fulfillment of normative rights in the event of unilateral termination of employment with the objectives of labor law. This research uses the normative legislative hierarchical research method as one of the research approaches used by the author by examining the legislative regulations that are related to the content of the researched hierarchy. The results of the study show that from several changes to Law No. 6 of 2023 concerning Job Creation in Fulfilling Workers' Normative Rights when Unilateral Termination occurs, it is still not in accordance with the Objectives of Labor Law, because there are still overlapping regulations regarding employment, especially unilateral termination of employment and the stipulation of the Law is considered too fast without going through the Omnibus Law so that it is not coherent with the Objectives of Labor Law and the changes are still based on other laws.